PEMBERDAYAAN MASYARAKAT MELALUI GERAKAN BERSAMA AMANKAN KEHAMILAN (GEBRAK) - Suprapti .; Surachmindari .; Ardi Panggayuh (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2019)
The joint movement program to safeguard pregnancy and childbirth (Gerakan Bersama Amankan Kehamilan dan Persalinan, GEBRAK) is a policy of the East Java Provincial Office that was launched through the assistance of pregnant women, childbirth by optimizing the use of the MCH Handbook. The purpose is to monitor the condition of pregnant women, childbirth to neonates to conduct monitoring and screening early on any changes that occur. Thus it is expected to reduce the occurrence of maternal mortality (MMR) or infant mortality (IMR). GEBRAK application was carried out in the Puskesmas Dinoyo involving 40 pregnant women with screening scores of 19 pregnant women (47.5%) with a low risk category while 7 pregnant women (17.5%) with high risk categories. All pregnant women get assistance starting from pregnancy, childbirth and babies aged 42 days